Elusive adulthoods : the anthropology of new maturities - Durham, Deborah Lynn, 1958-; Solway, Jacqueline S. (Indiana University Press, 2017)
Over the past decade, complaints about an inability to achieve adulthood have rung out around the world. Young people across the globe, burdened with debt and unsatisfactory job prospects, are struggling to establish households, marry, and, perhaps most significantly, "feel" grown up. For them, achievement of adulthood has become increasingly elusive. Elusive Adulthoods poses the question "What is adulthood?" and examines how the field of anthropology has come to overlook this meaningful life transition. Through diverse case studies, contributors explore a variety of means by which adulthood can be recognized, such as negotiated relationships with others and as a form of upward class mobility. Contributors also grapple with the difficulties that come from a sense of having missed full adulthood - perhaps due to rapid social change or reluctance to embrace the necessary subordination to job and family. In each case, changing political and economic factors form the background for generational experiences and understandings of what it means to reach adulthood as globalization dictates changes to traditional rites of passage. -- from back cover